The interaction between subclinical psychotic experiences, insomnia and objective measures of sleep - Cosgrave, J; Haines, R; van Heugten-van der Kloet, D; Purple, R; Porcheret, K; Foster, R; Wulff, K (Elsevier, 2017)
Investigations into schizophrenia have revealed a high incidence of comorbidity with disturbed sleep and circadian timing. Acknowledging this comorbidity on a dimensional level, we tested prospectively whether subclinical psychotic symptoms are more prevalent in individuals with insomnia. An insomnia group (n = 21) and controls (n = 22) were recruited on their subjective sleep quality, recorded actigraphically for 3 weeks and assessed for psychotic-like experiences with The Prodromal Questionnaire-16. Using multivariate Poisson regression analyses, we found that objective and subjective sleep measures interact to predict the highest risk for psychotic experiences. Objective measures of sleep and statistical modelling are rarely used in either clinical trials or practice for schizophrenia, yet this study highlights their value in these areas.